To Sleep in a Sea of Stars - Book 1 - Paolini, Christopher (New York : Tor, 2020)
A space voyager living her dream of exploring new worlds lands on a distant planet ripe for colonization before her discovery of a mysterious relic transforms her life and threatens the entire human race.
Keywords: Women explorers -- Fiction; Human-alien encounters -- Fiction; Relics -- Fiction; Space colonies -- Fiction; Space warfare -- Fiction; Imaginary places -- Fiction; Science fiction; Space operas (Fiction)